A novel method for assessing time zero of cementitious pastes using ultrasonic pulse in corrugated tubes (UPCT) - Aviz Palma e Silva Arthur; Santos Karyne; Capuzzo Valdirene; Bettencourt Ribeiro Antonio; Pereira Custódio João (MATEC Web of Conferences, 2025)
The Time Zero in cementitious mixtures marks the transition from a fluid suspension to a rigid structure, a critical phase for shrinkage analysis. This paper proposes a novel technique to measure Time Zero in cementitious materials through Ultrasonic Pulse in Corrugated Tubes (UPCT), originally used for autogenous shrinkage measurements. The corrugated tube design enables ultrasonic wave transmission while accommodating material deformation, preventing loss of contact due to volumetric changes. Cement pastes with a 0.35 water-to-binder ratio were tested, including a reference mixture with Portland cement and a second mixture incorporating 0.3% of a superabsorbent polymer (SAP). Time Zero was determined through ultrasonic pulse propagation time, VICAT needle penetration, and autogenous shrinkage tests using corrugated tubes. Results indicate that, for the reference mix, time-zero measurements were consistent across all methods, validating the ultrasonic approach proposed. However, in the SAP-modified mix, discrepancies arose, particularly in Vicat results, suggesting a delayed mechanical stiffening process. In cement paste with SAP, the reserve of water that the polymer allows, which is then released as hydration continues, may explain the observed delay in the kinetics of solid formation and is responsible for the reduction in autogenous shrinkage. These findings highlight the effectiveness of ultrasonic techniques in measuring the global structural evolution of cementitious materials. Nevertheless, variations in mixture composition and hydration mechanisms may compromise the reliability of certain methods, such as Vicat needle penetration, for accurately determining the transition to the hardening stage in cementitious materials.